2019
DOI: 10.3233/wor-192894
|View full text |Cite
|
Sign up to set email alerts
|

The psychological mechanism linking employee work engagement and turnover intention: A moderated mediation study

Abstract: BACKGROUND: In the global economy, motivating people to engage and stay in their work is a challenge for organizations. Researchers are increasingly recognizing the need for promoting strong employee engagement in the workplace. OBJECTIVE: This paper examines the effect of employee work engagement on turnover intention. The study focuses on the mediating role of trust that underpins the relationship between employee work engagement and turnover intention, and the moderating role of job embeddedness in influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 76 publications
5
52
0
2
Order By: Relevance
“…More precisely, Bailey et al (2017) asserted that highly engaged employees have a lower level of turnover intention and enhanced performance. This is further supported by a recent study made by Rafiq et al (2019) who examined the mechanism linking work engagement to employee intention to leave in the media sector in Pakistan. Authors found out that work engagement turnover intention were negatively correlated while highlighting the contribution of trust on turnover intention reduction.…”
Section: Frontline Engagement Relationship To Employees' Intention To Quitsupporting
confidence: 61%
“…More precisely, Bailey et al (2017) asserted that highly engaged employees have a lower level of turnover intention and enhanced performance. This is further supported by a recent study made by Rafiq et al (2019) who examined the mechanism linking work engagement to employee intention to leave in the media sector in Pakistan. Authors found out that work engagement turnover intention were negatively correlated while highlighting the contribution of trust on turnover intention reduction.…”
Section: Frontline Engagement Relationship To Employees' Intention To Quitsupporting
confidence: 61%
“…According to the conservation of resources (COR) theory [16], people with more powerful psychological forces may be better equipped to cope with stressors emerging from adverse work conditions, as the perceived threat of losing valuable resources is relatively low. Scholars have revealed that, in turbulent times, embedded employees are less motivated to leave their jobs and feel more satisfied with their life because their abundant resources reduce their sense of anxiety [17,18]. Following this theoretical logic, we further argue that job embeddedness that reflects a collection of critical psychological resources [19] should be taken into consideration when identifying key moderators of JI–LS relations in an insecure or unstable work environment.…”
Section: Introductionmentioning
confidence: 91%
“…Scholars believed that work engagement is one of the primary factors leading to a sense of happiness at work [82]. Conversely, voluntary turnover is still a challenge toward organizational management because it may involve significant costs such as loss of professional human resources, increasing expenditure of recruiting and training replacement, and worsening service quality [83][84][85].…”
Section: The Moderating Role Of Perceived Corporate Hypocrisymentioning
confidence: 99%
“…To prevent potential confounding effects, this study used age, sex, education, and organizational tenure as control variables. The reason was that previous studies showed these variables may influence outcome variables [12,82,104].…”
Section: Control Variablesmentioning
confidence: 99%